21
$\begingroup$

Let $[x]_q=\frac{1-q^x}{1-q}$, $[n]_q!=[1]_q[2]_q\cdots[n]_q$ and ${\binom{x}{n}}_{q}=\frac{[x]_q[x-1]_q\cdots[x-n+1]_q }{[n]_q!}$.

Computer experiments suggest that $$\det \left(q^\binom{i-j}{2}\left(\binom{i+r}{j}_{q}x+\binom{i+r-j}{j}_{q}\right)\right)_{i,j = 0}^{n - 1} = (1+x)^n$$

Any idea how to prove this?

$\endgroup$
  • 7
    $\begingroup$ I couldn't decide whether to upvote for an interesting question, downvote for a terrible pun, or try to upvote twice as appreciation for the terrible pun. :) $\endgroup$ – Joe Silverman Sep 17 at 14:40
  • 10
    $\begingroup$ "q-rious and q-riouser," by S. Ole Warnaar and Wadmin Zudlin. $\endgroup$ – Joseph O'Rourke Sep 17 at 15:42
  • 8
    $\begingroup$ @JosephO'Rourke's reference, clickable: Warnaar and Zudlin - $q$-rious and $q$-riouser. $\endgroup$ – LSpice Sep 17 at 16:00
  • 3
    $\begingroup$ Is there no q-re for these puns? $\endgroup$ – Gerry Myerson Sep 17 at 22:15
  • 3
    $\begingroup$ Someone ought to q-rate these comments. $\endgroup$ – Michael Engelhardt Sep 18 at 3:39
4
$\begingroup$

Let $A_n$ be the matrix involved in the problem and let $L_n=\left((-1)^{i-j}\binom{i}{j}_q\right)_{i,j=0}^{n-1}$. Observe that $L_n$ is lower-triangular with 1's in the diagonal. Multiplying, we have: $$L_nA_n=\left(x\,u_{i,j}(r)+u_{i,j}(r-j)\right)_{i,j=0}^{n-1}$$ where $$u_{i,j}(r)=\sum_{k=0}^i(-1)^{i-k}q^{\binom{k-j}{2}}\binom{i}{k}_q\,\binom{k+r}{j}_q\,.$$

Now \begin{eqnarray*} u_{i,j}(r)&=&\sum_{k=0}^i(-1)^{i-k}q^{\binom{k-j}{2}}\binom{i}{i-k}_q\,\binom{k+r}{k+r-j}_q \\ &=&(-1)^{r+i-j}\,q^{\binom{r+1}{2}}\,\sum_{k=0}^i q^{k(k+r-j)}\binom{i}{i-k}_q\,\binom{-j-1}{k+r-j}_q \\ &=&(-1)^{r+i-j}\,q^{\binom{r+1}{2}}\,\sum_{k=0}^i q^{k(k+r-j)}\binom{i}{i-k}_q\,\binom{-j-1}{k+r-j}_q \\ &=&(-1)^{r+i-j}\,q^{\binom{r+1}{2}}\,\binom{i-j-1}{i-j+r}_q =q^{\binom{i-j}{2}}\,\binom{r}{j-i}_q\,. \end{eqnarray*} Hence $u_{i,j}(r)=0$ when $i>j$ and $u_{i,i}(r)=1$. Thus $L_nA_n$ is upper triangular with $x+1$ as elements of the diagonal.

$\endgroup$
6
$\begingroup$

In the mean-time I have found a proof:

First write Vandermonde’s identity $$\sum_{j=0}^k q^{(k-j)(i+r-j)}\binom{s-r}{k-j}_{q}\binom{i+r}{j}_{q}=\binom{i+s}{k}_{q}$$ in the form $$\sum_{j=0}^k q^{\frac{(j-k)(j-k-1-2r)}{2}}\binom{s-r}{k-j}_{q}q^{\binom{i-j}{2}}\binom{i+r}{j}_{q}=q^{\binom{i-k}{2}}\binom{i+s}{k}_{q}$$ and then replace $s$ by $r-k.$ The elements of the first column of the matrix $$A_{n}=\left(q^\binom{i-j}{2}\left(\binom{i+r}{j}_{q}x+\binom{i+r-j}{j}_{q}\right)\right)_{i,j = 0}^{n - 1} $$ are $q^\binom{i}{2}(x+1).$ By linearity we get $\det{A_n}=(x+1)\det{B_n}$, where the first column of $B_n$ consist of the numbers $q^{\binom{i}{2}}$.
Then by the above identity we can reduce the second column to $q^{\binom{i-1}{2}}\binom{i+r}{1}_{q}(1+x)$ and again factor out $(1+x)$. Iterating this procedure we get $\det{A_n}=(x+1)^n\det{C_n}$ with $C_n= \left(q^\binom{i-j}{2}\binom{i+r}{j}_{q} \right)_{i,j = 0}^{n - 1}$.

To prove $\det{C_n}=1$ observe that $$q^{\binom{i+1-j}{2}}\binom{i+1+r}{j}_{q}-q^{i}q^\binom{i-j}{2}\binom{i+r}{j}_{q}=q^\binom{i-(j-1)}{2}\binom{r+i}{j-1}_{q}.$$ Therefore by subtracting $q^{i}$ times row $i$ from row ${i+1}$ we get that $\det{C_n}= \det{ \begin{pmatrix} 1& * \\ 0 & C_{n-1} \end{pmatrix}}=\dots=1.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.